The Influence of Artificial Intelligence on the Teaching of Environmental Art Design Major in Colleges and Universities - Chen, Qixin (International Journal of Social Sciences and Public Administration, 2025)
This paper summarizes the application of artificial intelligence in the field of environmental art design, including computer-aided design, virtual reality and augmented reality and other technologies, and expounds its auxiliary role in teaching, such as the integration of teaching resources, teaching mode reform and the cultivation of innovation ability. Secondly, this paper analyzes the influence of artificial intelligence on the teaching of environmental art design majors in universities, including the changes in teaching concept, teaching content, teaching methods and teachers’ roles. Then, this paper discusses the challenges faced by the teaching of environmental art design in universities under the artificial intelligence environment, such as rapid technology update, construction of teachers, allocation and integration of educational resources and adjustment of talent training mode, and puts forward corresponding countermeasures. Finally, the future development of artificial intelligence in environmental art design teaching in universities, such as the further development of artificial intelligence technology, the trend of education informatization and intelligence, as well as cross-border integration and innovation.